Diversified Security in Uncertain Conditions: An Investigation of Risk Transfer Among Bitcoin, Gold, Dollar, and Fixed-Income Funds in Iran in the Presence of Geo-Political Risk – A TVP-VAR Approach - Vahid Omidi; Negin Maqsudi (راهبرد مدیریت مالی)
Given the occurrence of international uncertainties and their direct impact on individuals' investment portfolios, investors, based on their preferences, tend to accept the minimum level of risk and diversify their risks while maximizing returns. In such circumstances, in the face of uncertainty, identifying safe assets becomes crucial. The present study examines the risk transfer among Bitcoin, gold, the dollar, and fixed-income funds in Iran, considering geopolitical risk. Daily data from August 2, 2021 to October 21, 2023 are used, employing the TVP-VAR approach. Initially, by investigating heterogeneous assets in the portfolio, the study identifies the relationships among the assets. Subsequently, by adding geopolitical risk to the model, the safest asset in the portfolio is re-determined. Safe assets are then declared in the face of geopolitical risk, and investments in these assets are recommended if necessary. The results indicate that gold has been a safe asset compared to other portfolio assets during times of uncertainty and has been able to impact the overall network. Additionally, Bitcoin is introduced as a safe asset in the face of geopolitical risk.